Pricing of commodity derivatives on processes with memory - Fred Espen Benth; Asma Khedher; Michèle Vanmaele (Risks, 2020)
Spot option prices, forwards and options on forwards relevant for the commodity markets are computed when the underlying process S is modelled as an exponential of a process xi with memory as, e.g., a Volterra equation driven by a Levy process. Moreover, the interest rate and a risk premium rho representing storage costs, illiquidity, convenience yield or insurance costs, are assumed to be stochastic. When the interest rate is deterministic and the risk premium is explicitly modelled as an Ornstein-Uhlenbeck type of dynamics with a mean level that depends on the same memory term as the commodity, the process (xi; rho) has an affine structure under the pricing measure Q and an explicit expression for the option price is derived in terms of the Fourier transform of the payoff function.
Keywords: 330; affine processes; commodity markets; derivatives pricing; equivalent measures; Fourier transform; Langevin equation